Penerapan Bauran Promosi Pada PT. Wan Teknologi Internasional - Muhammad Difa Fahreza; Yulia Nurendah; Morita Morita (Jurnal Aplikasi Bisnis Kesatuan, 2023)
Indonesia is a very potential market. Data from the Ministry of Communication and Information stated that the number of internet users was 112.6 million people, and most of them were aged 17-23 years. This shows that the majority of the productive age population in Indonesia are internet users. The purpose of writing this final project is to find out: 1) How is the application of the promotion mix at PT. International Technology Wan; 2) What are the constraints faced in implementing the promotion mix; 3) How to overcome obstacles in implementing the promotion mix. The results of writing this final project are: 1) The promotion mix is carried out in the form of advertising by advertising on websites, sales promotion by giving discounts, direct marketing by sending emails to companies, word of mouth by creating positive word of mouth, interactive marketing by using social media and website as a medium for interaction with customers, events and sponsorship by participating in exhibitions and product launching events; 2) Constraints in the implementation of the promotion mix, namely: advertising does not run smoothly, difficulties in determining the time and duration of promos, monotonous mailing formats, difficulty controlling the effectiveness of word of mouth, brand awareness and corporate image have not been optimally formed, limited content ideas; 3) Solutions in dealing with obstacles within the company, namely increasing creativity in the types of advertisements displayed, formulating promos to be released and determining the duration of time based on discussions between related divisions, increasing creativity in the email format sent, distributing questionnaires related to product knowledge, increasing consumer involvement in content creation so that the content produced is content needed by consumers and can increase consumer curiosity regarding the services offered, become sponsors and participate in events related to and aligned with company services. Keywords: Promotion Mix, Technology